Topical estrogens: an update - Papadopoulos, A... J. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
Topical estrogens have been used for many different dermatologic conditions. Currently, they have reemerged as a form of estrogen replacement therapy for peri/postmenopausal women. In this article we review current applications and future indications for topical estrogen therapy, with an emphasis on the transdermal estrogen patch.
Keywords: Administration, cutaneous; Administration, topical; Estrogen replacement therapy; estrogeni; Estrogens; Forecasting; kožne bolezni; Progesterone; Skin absorption